2001
DOI: 10.1046/j.1365-2702.2001.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Women’s lived experience of breast biopsy: a phenomenological study

Abstract: This study aimed to explore Irish women's lived experience of breast biopsy with a view to gaining a deeper understanding of their individual experiences and the meanings that it holds for them. A phenomenological approach from a Heideggerian hermeneutical perspective was used. Study participants were eight women aged 22-54 years who had experienced a recent breast biopsy with benign diagnosis. Data were collected using in-depth interviewing. The work of Benner (1994), together with guidelines from Morse & Fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 33 publications
5
57
0
Order By: Relevance
“…The strategy these latter patients adopted to cope with the wait was to distance themselves from the operation and also to seek support from close relatives. Similar findings were derived from a study of women waiting for breast biopsy (O'Mahony 2001).…”
Section: Discussionsupporting
confidence: 83%
“…The strategy these latter patients adopted to cope with the wait was to distance themselves from the operation and also to seek support from close relatives. Similar findings were derived from a study of women waiting for breast biopsy (O'Mahony 2001).…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have shown that the period surrounding the diagnosis of breast cancer is one of the most stressful times for women and their partners [23][24][25][26][27]. In our series, 51% of the final histological diagnoses were benign and 49% were malignant.…”
Section: Discussionmentioning
confidence: 63%
“…20,21 Therefore, uncertainty can be regarded as the result of a stress event experienced by women waiting for diagnosis. 4,6,20 Uncertainty can also be seen as a source of stress after diagnosis for women facing issues such as probable breast cancer in the future, survival rate, and recurrence. 4 In general, uncertainty is lower for women with less physical disturbance, higher selfperceived seriousness of the illness, older age, and more education and for single women.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…13,15 Although levels of overall uncertainty, ambiguity, and complexity uncertainty before a breast biopsy and upon notice of a breast biopsy were not significantly different, the uncertainty level before a breast biopsy was slightly higher. The reason for this slight difference may be that aside from the threat of a breast cancer diagnosis, 6 women were not familiar with the biopsy process. 23 This point is supported by the authors' previous study 34 indicating that women with suspected breast cancer have higher information needs before than after breast biopsy.…”
Section: Predictive Factors For Uncertaintymentioning
confidence: 99%